PENGARUH KEPEMILIKAN INSTITUSIONAL, MANAJERIAL, FREE CASH FLOW PADA NILAI PERUSAHAAN DENGAN VARIABEL INTERVENING KEBIJAKAN HUTANG - Dwi Safitri Sadia, Ni Made; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
The value of company is a proxy that describes the prosperity of our shareholders. This study aimed to get empirical evidence of institutional ownership, managerial ownership and free cash flow in the value of the company with the debt policy as intervening variable. The location of this research manufacturing companies listed in Indonesia Stock Exchange 2013-2015. The population of this study were 93 companies that obtained by using purposive sampling technique. The analysis technique used is path analysis. The results showed that the free cash flow positive effect on debt policy, managerial ownership negative effect on the value of the company, the debt policy has positive effect on the value of the company, the debt policy cannot afford mediates the effect of institutional ownership in the company's value and managerial ownership on enterprise value, debt policy is able to mediate the effect of free cash flow in the company's value.
Keywords: Institutional Ownership, Managerial Ownership, Free Cash Flow, Debt Policy, Corporate Value